1988
DOI: 10.1128/mcb.8.11.4625
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of cytochrome c expression during the developmental cycle of Trypanosoma brucei.

Abstract: We examined the expression of a nucleus-encoded mitochondrial protein, cytochrome c, during the life cycle of Trypanosoma brucei. The bloodstream forms of T. brucei, the long slender and short stumpy trypanosomes, have inactive mitochondria with no detectable cytochrome-mediated respiration. The insect form of T. brucei, the procyclic trypanosomes, has fully functional mitochondria. Cytochrome c is spectrally undetectable in the bloodstream forms of trypanosomes, but during differentiation to the procyclic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…4A). In addition, there is evidence that the developmental regulation of expression of cytochrome c and cytochrome c reductase is due to degradation of the proteins in the bloodstream form, perhaps because of failure of mitochondrial import (65,66,77,78). Experiments with trypanosomes with a soluble protein containing an N-terminal targeting signal for the mitochondrial matrix, and a C-terminal glycosomal targeting signal, have also shown that such signals can compete (28).…”
Section: Discussionmentioning
confidence: 99%
“…4A). In addition, there is evidence that the developmental regulation of expression of cytochrome c and cytochrome c reductase is due to degradation of the proteins in the bloodstream form, perhaps because of failure of mitochondrial import (65,66,77,78). Experiments with trypanosomes with a soluble protein containing an N-terminal targeting signal for the mitochondrial matrix, and a C-terminal glycosomal targeting signal, have also shown that such signals can compete (28).…”
Section: Discussionmentioning
confidence: 99%
“…A similar analysis of mitochondrial encoded proteins led to the identification of an alternatively edited COIII mRNA that encoded a component of the FKC (32,40). The developmental regulation of nuclear-encoded mitochondrial proteins in T. brucei occurs principally at the level of RNA stability and, to a lesser extent, by differential protein stability (41,42). High-throughput RNA sequencing (RNA-Seq) provides an accurate evaluation of the life cycle-dependent expression of mitochondrial proteins (43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
“…Procyclic (insect) form parasites contain a fully functional mitochondrion that carries out oxidative phosphorylation (3,29,42). In contrast, bloodstream (mammalian) form trypanosomes exhibit a high rate of glycolysis and contain an underdeveloped mitochondrion (3,29,42). Similar to other eukaryotes, the genes for the mitochondrial proteins are encoded both in the nuclear and mitochondrial genomes.…”
mentioning
confidence: 92%
“…It contains a single large mitochondrion, whose gene expression and metabolic activity are regulated throughout its life cycle. Procyclic (insect) form parasites contain a fully functional mitochondrion that carries out oxidative phosphorylation (3,29,42). In contrast, bloodstream (mammalian) form trypanosomes exhibit a high rate of glycolysis and contain an underdeveloped mitochondrion (3,29,42).…”
mentioning
confidence: 99%